Encouraging Student Interest in Teaching Through a Medical Student Teaching Competition. (August 2017) - DeSimone, Ariadne K.; Haydek, John P.; Sudduth, Christopher L.; LaBarbera, Vincent; Desai, Yaanik; Reinertsen, Erik; Manning, Kimberly D.
Abstract : Problem: Clinician educators have realized the value not only of assigning teaching roles to medical students but also of offering explicit training in how to teach effectively. Despite this interest in the development of medical students' teaching skills, formal teaching instruction and opportunities for practice are lacking. Approach: To encourage medical student interest in teaching, the authors developed and implemented a medical student teaching competition (MSTC) at Emory University School of Medicine during the summers of 2014, 2015, and 2016. Each year, eight student finalists were each paired with a physician "teaching coach" and given one month to prepare for the MSTC. During the competition, each finalist delivered an eight-minute presentation to a panel of seven physician and resident judges. The authors describe the development, implementation, and assessment of the MSTC. Outcomes: Approximately 150 medical students and faculty members attended the MSTC each year. The students in attendance felt that the MSTC made them more likely to seek out opportunities to learn how to teach effectively and to practice teaching. Additionally, some students are now more interested in learning about a career in academic medicine than they were before the MSTC. Next Steps: Given the need for more formal initiatives dedicated to improving the teaching skills of doctors-in-training, including medical students, innovative solutions such as the MSTC may enhance a medical school's existing curriculum and encourage student interest in teaching. The MSTC model may be generalizable to other medical schools.